Utilizing a cognitive engineering approach to conduct a hierarchical task analysis to understand complex older adult decision-making during over-the-counter medication selection. - Morris, Ashley O.; Gilson, Aaron; Chui, Michelle A.; Xiong, Ka (Research in Social & Administrative Pharmacy, 2021)
Background: Adults aged 65+ (older adults) disproportionately consume 30% of over-the-counter (OTC) medications and are largely responsible for making OTC treatment decisions because providers lack awareness of their consumption. These treatment decisions are complex: older adults must navigate age-related body/cognitive changes, developed comorbidities, and complex medication regimens when selecting the right OTC. Yet little is known about how older adults make such decisions.Objectives: This study characterizes older adults' cognitive decision-making process when seeking to self-medicate with OTCs from their community pharmacy, and demonstrates how hierarchical task analysis (HTA) can be used to evaluate a pharmacy intervention's impact on their decision-making.Methods: A pre-/post-implementation approach, using a think-aloud interview process, was conducted with older adults within a community pharmacy setting as they completed a hypothetical scenario to treat either pain, sleep, or cough/cold/allergy symptoms. HTA developed a conceptualization of older adult decision-making regarding OTC selection and use before/after Senior Section implementation.Results: An HTA constructed from 12 purposefully-selected interviews (pre-n = 9/post-n = 3), consisting of 8 goals/15 sub-goals. While selecting an OTC, older adults considered quantity, cost, form, regimen, safety, strength, appropriateness of OTC safety, generic/name-brand, past experiences, and ingredients. The intervention reduced by half the number of factors considered.Implications: Older adult decision-making is more complex than just selecting OTC medication from a pharmacy shelf. HTA-informed decision profiles can provide pharmacists critical insights into safety issues that older adults may not be considering (e.g., factors related to safety, strength, or appropriateness of OTC for symptoms) so that pharmacists can support their decision-making.